ANALISIS KADAR LOGAM BERAT TIMBAL PADA GARAM KONSUMSI MENGGUNAKAN METODE SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Astika, Tri (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
Iodized salt is a type of consumption salt. Consumption salt before being circulated needs to be tested first according to the quality standards of consumption salt. In this study, heavy metal lead content was tested using atomic absorption spectrophotometry (SSA) method. The purpose of this study is to determine the level of heavy metal lead in table salt based on the Indonesian National Standard (SNI). Research methods using tools used in this study are 100 ml beaker, 500 ml volumetric flask, 250 ml Erlenmeyer, 200 ml Erlenmeyer, spatula, stirring rod, PH meter, separating funnel, filter paper, spray bottle, 2 ml measuring pipette, 5 ml measuring pipette, drop pipette, Atomic Absorption Spectrophotometry (SSA). The materials used in this study are HNO3, distilled water, coarse salt, fine salt. The results of heavy metal lead levels in sample A amounted to 1.26 ppm, sample B 1.13 ppm, sample C 3.08 ppm and sample D amounted to 2.88 ppm. Based on these results, it has met the quality standards of consumption salt according to Indonesian national standards.